Outcomes of Retrograde Intrarenal Surgery Performed Under Neuraxial vs. General Anesthesia: An Updated Systematic Review and Meta-Analysis - Duan, Mingda; Chen, Yu; Sun, Li (Frontiers in Surgery, 2022)
Background: The current review aimed to assess if the outcomes of retrograde intrarenal surgery (RIRS) differ with neuraxial anesthesia (NA) or general anesthesia (GA). Methods: The databases of PubMed, Embase, CENTRAL, ScienceDirect, and Google Scholar were searched up to 3rd December 2021 for randomized controlled trials (RCTs) and observational studies comparing outcomes of RIRS with NA or GA. Results: Thirteen studies involving 2912 patients were included. Eight were RCTs while remaining were observational studies. Meta-analysis revealed that stone free status after RIRS did not differ with NA or GA (OR: 0.99 95% CI: 0.77, 1.26 I2=10% p=0.91). Similarly, there was no difference in operation time (MD: -0.35 95% CI: -4.04, 3.34 I2=89% p=0.85), 24 hour pain scores (MD: -0.36 95% CI: -0.96, 0.23 I2=95% p=0.23), length of hospital stay (MD: 0.01 95% CI: -0.06, 0.08 I2=35% p=0.78), Clavien-Dindo grade I (OR: 0.74 95% CI: 0.52, 1.06 I2=13% p=0.10), grade II (OR: 0.70 95% CI: 0.45, 1.07 I2=0% p=0.10) and grade III/IV complication rates (OR: 0.78 95% CI: 0.45, 1.35 I2=0% p=0.37) between NA and GA. Except for grade I complications, the results did not change on subgroup analysis based on study type and NA type. Conclusion: Our results suggest that NA can be an alternative to GA for RIRS. There seem to be no difference in the stone-free rates, operation time, 24-hour pain scores, complication rates, and length of hospital stay between NA and GA for RIRS. Considering the economic benefits, the use of NA may be preferred over GA while taking into account patient willingness, baseline patient characteristics, and stone burden.